2018
DOI: 10.1155/2018/7949741
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint of Recycled Aggregate Concrete

Abstract: Carbon footprint is one of the most widely used tools for assessing the environmental impacts of the production and utilization of concrete as well as of the components derived from it, representing the amount of carbon dioxide and other greenhouse gases associated with this product, expressed as CO2 equivalents. In this paper, carbon footprint was used to compare the environmental performance in the production phase of a concrete made with both recycled and crushed virgin limestone aggregates, using a life cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 14 publications
0
23
0
2
Order By: Relevance
“…Results indicated that the limestone aggregates contained a high magnesium percentage (Mg) as shown in Figure 2b. According to the literature [7,33,34], this could correspond to a type of aggregate not clastic, coming from sedimentary crushed rocks called dolomite.Therefore, it is a carbonate mineral (calcium magnesium carbonate, CaMg(CO3)2) formed by chemical or biological precipitations from seawater reacting with CaCO3, whose main components are calcite and dolomite. The X-ray diffraction analysis of the aggregates shows that the characteristic peaks corresponded to the crystalline structure of calcite and dolomite, as is possible to observe in Figure 3.…”
Section: Cementitious Composites (Mortars)mentioning
confidence: 99%
“…Results indicated that the limestone aggregates contained a high magnesium percentage (Mg) as shown in Figure 2b. According to the literature [7,33,34], this could correspond to a type of aggregate not clastic, coming from sedimentary crushed rocks called dolomite.Therefore, it is a carbonate mineral (calcium magnesium carbonate, CaMg(CO3)2) formed by chemical or biological precipitations from seawater reacting with CaCO3, whose main components are calcite and dolomite. The X-ray diffraction analysis of the aggregates shows that the characteristic peaks corresponded to the crystalline structure of calcite and dolomite, as is possible to observe in Figure 3.…”
Section: Cementitious Composites (Mortars)mentioning
confidence: 99%
“…Recycling the waste concrete and bricks into recycled aggregate (RA) is the most effective method of reducing the amount of construction and demolition (C&D) wastes, which meets the sustainable development of construction industry [31,32]. e chloride permeability of recycled aggregate concrete (RAC) has been investigated by many scholars, and the results highlight that the addition of RA increases the chloride permeability [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Construction demolition waste (CDW) stems from construction, renovation, and demolition workplaces which include (i) excavation materials, (ii) road building and maintenance materials, (iii) demolition materials, and (iv) other worksite waste materials, (e.g., unpainted, non-treated wood scrap, unpainted, non-treated wood pallets, plastic, packaging), land clearing, and development activities [ 72 ]. Construction waste is increasing in volume and affecting the environment adversely [ 73 ]. Over 80% of CDW is composed of excavated earth in construction works.…”
Section: Carbon Footprint Of Construction and Demolition Waste Generation And Ghg Reductionmentioning
confidence: 99%